Impact of Hormonal Contraceptives on Splenic Architecture and Cytokine Response in Neisseria gonorrhoeae-Infected mice - Pooja, Pooja; Srivastava, Nidhi; Sethi, Sunil; Dhatwalia, Sunil Kumar (Journal of Neonatal Surgery, 2025)
Neisseria gonorrhoeae is a Gram-negative bacterium causing gonorrhea, a sexually transmitted infection. To study the effect of combined oral contraceptives(COC) on the immune response of mice, we selected the key lymphoid organ, spleen which is known to integrate innate and adaptive immunity and is sensitive to hormonal and environmental influences. Female BALB/ c mice were divided into 4 groups named as COC Treated(T), Infected with N. gonorrhoeae (I), COC Treated Infected(TI), and Control where mice were kept without any treatment (C). The spleen's histological examination showed that although infection alters the splenic structure, leading to amyloidosis, hemosiderin buildup, and a loss of red and white pulp differentiation, pretreatment of the group with COC only led to decreased cellularity and structural disarray of splenic compartments. MDA levels in the TI group were stable, indicating a compensatory antioxidant response. SOD activity was significantly decreased in the T group, but remained insignificantly altered in the I & TI group. Catalase activity dropped insignificantly in all groups, indicating a disabled H2O₂ detoxification system. while GSH levels remain maintained. These results indicate that infection and COC perturb the splenic redox balance, but in combination may activate adaptive antioxidant systems. Limited inflammatory response in spleen during Neisseria gonorrhoeae infection was observed. TNF- α levels declined, suggesting host adaption. COC treatment and bacterial infection maintained high IL- 1β levels, while TI suppressed inflammatory action and delayed pathogen clearance. An, in general, upregulation of IFN-γ in TI group suggests inactivation of cell mediated immunity. The minimum IL- 10 induction in all groups indicates inadequate anti-inflammatory regulation.